PROBLEMS AND POSSIBILITIES OF KNOWLEDGE TRANSFER: A CASE STUDY ON POWEL ENERGY MANAGEMENT AB - Mohammad Monoar Hossain (Universitas Trisakti, 2009)
This study identifies problems, and recommends solutions within the realm of knowledge transfer in Powel Energy Management AB. The focus is on knowledge transfer on the inter-organizational level between the Swedish subsidiary and the Norwegian parent company. The study is based on data collected during interview with leading representatives from the Norwegian and Swedish organizations. The analysis is based on Davenport and Prusak's (1998) seven knowledge transfer hurdles in combination with Wang's (2004) model for knowledge transfer between parent company and subsidiary. The two key problems, which have been identified, are the parent company's moderate capacity to transmit knowledge and the subsidiary's moderate intent to learn. The author's recommendations consist of seven actions: 1) Use the word knowledge, 2) Disperse the knowledge base in the development team, 3) Create a direct link between the developers in Norway and business units in Sweden, 4) Make developers work in the selling and consulting environment, 5) Make the developers introduce new software features, 6) Increase usage of video conferencing, and 7) Introduce rewards for knowledge transfer.Key Words: Knowledge management, Knowledge transfer, Knowledge sharing.